1982
DOI: 10.1161/01.hyp.4.3_pt_2.43
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of vascular sodium-potassium pump activity to intracellular sodium in hypertensive rats.

Abstract: SUMMARYThe activity of the sodium-potassium (Na + -K + ) pump in arterial tissue from rats with chronic DOCA-salt or one-kidney Grollman renal hypertension was assayed in ritro as the rate of ouabaln-sensltive M Rb + uptake. Estimates of total cell Na + and tissue K + were made by a lithium-substitution method on the same segment of arterial tissue. In both freshly excised tail arteries and aortas, and in aortas after overnight cold storage at 4° C and a 3-hour equilibration at 37° C in Krebs-Henseleit, cell N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…These relaxation responses are blocked by ouabain and by K +free solution. These observations, along with those of Brock et al, (1982), suggest that the results that we have observed with the dog LAD may be a generalized effect of monensin on vascular smooth muscle.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These relaxation responses are blocked by ouabain and by K +free solution. These observations, along with those of Brock et al, (1982), suggest that the results that we have observed with the dog LAD may be a generalized effect of monensin on vascular smooth muscle.…”
Section: Discussionsupporting
confidence: 82%
“…Ouabain blocked the hyperpolarization in both experiments. Recently Brock et al (1982) have measured Na + ,K + -ATPase activity in rat aorta using the ouabain-sensitive ^Rb" 1 " uptake method. They found that monensin increased 86 Rb + uptake in rat aortic smooth muscle by increasing total cell sodium.…”
Section: Discussionmentioning
confidence: 99%
“…1980;Songu-Mize el al. 1982), increased (Friedman & Nakashima 1978;Brock et al 1982) and others have found no change (Stern et al 1984) in vascular Na,K ATPase activity. Stern et al ( 1 984) have suggested that these conflicting data probably reflect the opposing effects of sodium loading induced inhibition of Na,K ATPase activity and DOCAmediated stimulation of the enzyme.…”
Section: Discussionmentioning
confidence: 89%
“…Increasing intracellular Ca2+ was recently shown to augment passive Na+ influx in cultured human fibroblasts and MDCK cells (Rindler et al, 1979;Villereal, 1981). An increase in Na+ influx in turn increases Na+/K+ pump activity, as was recently shown with Na+ ionophores in both cultured cells and intact arterial tissue (Smith and Rozengurt, 197813;Brock and Smith, 1982;Brock et al, 1982a). The stimulation of the pump would be expected to hyperpolarize the cell membrane, which might help to reestablish the Na+ gradient.…”
Section: Discussionmentioning
confidence: 78%